Disentangling Mechanisms Behind Chronic Lethality through Toxicokinetic–Toxicodynamic Modeling. (4th May 2021) - Gergs, André; Hager, Jutta; Bruns, Eric; Preuss, Thomas G.
Abstract: Ecotoxicological profiles of the 3 insecticides imidacloprid, thiacloprid, and flupyradifurone in terms of acute and chronic effects were analyzed in Chironomus riparius . Toxicokinetic–toxicodynamic modeling revealed that chironomids would die from starvation as a result of prolonged feeding inhibition under chronic exposures. The starvation effect is an indirect cause for mortality, which, for the neonicotinoids, adds to the direct/acute mortality, although the results suggests that this additional effect is not relevant for flupyradifurone. Environ Toxicol Chem 2021;40:1706–1712. © 2021 Bayer Inc. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.